Synthesis, molecular modeling, anti-cancer and COX-1/2 inhibitory activities of novel thiazolidinones containing benzothiazole core (Bangladesh Journal of Pharmacology, 2024)
In this study, new 1,3-thiazolidin-4-one derivatives containing arylmethylene groups in the 5-position were obtained from 6-(trifluoromethoxy)-1,3-benzothiazol-2-amine (riluzole). Synthesized compounds were characterized by spectral data and elemental analysis. In vitro, cytotoxic activities of the synthesized molecules were evaluated against the human lung cancer (A549) and human prostate cancer (PC-3) cell lines. Compounds were also tested on mouse embryonic fibroblast cells (NIH/3T3) to determine selectivity. Ten target compounds 3-12 were also screened for their COX-1 and COX-2 inhibitory activities. Of these compounds, 4 showed the highest COX-2 inhibition at 10 μM. Molecular docking calculations were performed to understand the binding interactions of compounds with COX-1 and COX-2 proteins. In silico studies of the tested compounds represented important binding modes that may be responsible for their anti-cancer activity via selective inhibition of the COX-2 enzyme. ADMET predictions were conducted to assess the drug-like properties of the novel compounds.